2017
DOI: 10.1111/aec.12534
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the invasive fungusAustropuccinia psidii(myrtle rust) on three Australian Myrtaceae species of coastal swamp woodland

Abstract: Exotic fungal pathogens can substantially affect individuals and populations of susceptible native plant species, potentially resulting in changes in community structure and composition. Austropuccinia psidii (myrtle rust) is a pathogenic fungus native to South America that affects species in the plant family Myrtaceae. The pathogen was introduced accidentally to Australia and first detected in NSW in April 2010. Ecological impacts have been poorly studied in the native range of A. psidii and even less in its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…It has been suggested that the between‐species variation may be a result of different susceptibilities, while the within‐species variation may be explained by differing climatic conditions, resource availability and number of re‐infection events between studies (Smith ). Also consistent with our results, Fernandez Winzer et al () reported that branching was not altered by A. psidii after a single inoculation event in the three coastal woodland species mentioned above. Because of this, it can be suggested that increased branching may only occur after successive reinfections of seedlings (that is, over a longer time period) or in plants at more advanced stages in their development (Fernandez Winzer et al ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It has been suggested that the between‐species variation may be a result of different susceptibilities, while the within‐species variation may be explained by differing climatic conditions, resource availability and number of re‐infection events between studies (Smith ). Also consistent with our results, Fernandez Winzer et al () reported that branching was not altered by A. psidii after a single inoculation event in the three coastal woodland species mentioned above. Because of this, it can be suggested that increased branching may only occur after successive reinfections of seedlings (that is, over a longer time period) or in plants at more advanced stages in their development (Fernandez Winzer et al ).…”
Section: Discussionsupporting
confidence: 93%
“…Also consistent with our results, Fernandez Winzer et al () reported that branching was not altered by A. psidii after a single inoculation event in the three coastal woodland species mentioned above. Because of this, it can be suggested that increased branching may only occur after successive reinfections of seedlings (that is, over a longer time period) or in plants at more advanced stages in their development (Fernandez Winzer et al ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Rust fungi (Pucciniales) constitute one of the largest groups of plant pathogens, with about 7,800 described species (Helfer, ), and some rust species can have large economic and ecological impacts. For example, myrtle rust ( Austropuccinia psidii ) is currently decimating a wide range of Myrtaceae around the world (Fernandez Winzer, Carnegie, Pegg, & Leishman, ; Glen, Alfenas, Zauza, Wingfield, & Mohammed, ), such as the endemic Eugenia koolauensis in Hawai‘i and the endemic Rhodamnia rubescens in native forests in Australia (Carnegie et al, ). Coffee leaf rust ( Hemileia vastatrix ) is substantially damaging Coffee plantations worldwide (Talhinhas et al, ).…”
Section: Introductionmentioning
confidence: 99%